Electrochemical and electrical characteristics of ball milled Cs2Ti6O13 modified by the surface-to-bulk migration of hydroxyl groups - Tosapol Maluangnont; Phieraya Pulphol; Kanisorn Klangvijit; Khemjiranee Bowornthommatadsana; Narong Chanlek; Makoto Ogawa; Winadda Wongwiriyapan (Dalton Transactions, 2023)
. The alternating current electrical properties were also measured, revealing fundamental insights such as the one-dimensional conduction pathway and the relaxation time in microseconds. A model has been proposed for this surface-to-bulk migration of the hydroxyl groups, which competes with surface dangling bonds leading to particle agglomeration.
Keywords: Nuclear materials and radiation effects; Advancements in Solid Oxide Fuel Cells; Ferroelectric and Piezoelectric Materials